Polifem między nomos oraz physis. Homer, Sofiści i „prawa ludzkiej miary” w dramacie satyrowym "Cyklop" Eurypidesa - Skarbek-Kazanecki, Jan (Collectanea Philologica, 2024)
At the height of their development and popularization, the Odyssey and the Iliad were part of a rich tradition of oral epic poetry. And while the transmission of Homer’s epics was facilitated by a Panhellenic framework, these works themselves became catalysts for the consolidation and unification of Greek culture; they shaped a shared Greek identity and a common value system. Particularly significant in this regard is the episode from Book IX of the Odyssey, namely the scene of the Odysseus-Polyphemos encounter. The island of the Cyclopes, as I argue in this article, represents a structural inversion of a civilized and orderly human community; the image of Polyphemos embodies “wildness” and delineates (or redefines) the boundaries of discourse on civilization, culture, and community. This motif anticipates, thus, the debate on nomos (“law”) and physis (“nature”) that engaged the intellectual elite of Athens, known as the sophists, around the turn of the 5th and 4th centuries BCE. This article traces the reception of the Polyphemos motif within this sophistic discourse of that period. Euripides’ satyr play Cyclops, filled with allusions to the sophists who were keenly interested in the Homeric motif of the island of the one-eyed monsters, serves as the focal point for this analysis. Furthermore, I will show that Euripides uses the dramaturgical framework inspired by Homer’s epic to confront two worldviews: on the one hand, respect for tradition and values associated with ancient poetry (the attitude represented by Odysseus), and on the other, the rationalism, radicalism, and tradition-directed criticism that characterized Euripides’ contemporary political thinkers and philosophers (represented by Polyphemos).